Another diaspora imaginaries: consumption, urbanity and post-peripheral events - Rosamaria Luiza de Melo Rocha; Josimey Costa da Silva; Simone Luci Pereira (Galáxia, 2015)
This paper introduces and discusses some phenomena which collaborate with the theoretical construction hereby called “the diasporic imaginaries”, signallers of post-peripheral dynamics and of cultural flow’s circulation. The post-peripheral scenario, which gives room to phenomena like the “rolezinhos”, “funk ostentação” and “pinta” in the city of Natal (RN), reveals subjects of action and speech who are capable of actuating among contexts of frontier.